PENGARUH FENOMENA SOSIAL FEAR OF MISSING OUT (FOMO) TERHADAP RENDAHNYA TANGGUNG JAWAB REMAJA SEBAGAI WARGA NEGARA MUDA DALAM PERSPEKTIF PENDIDIKAN KEWARGANEGARAAN : (Studi Survei di Kelas XI SMA PGRI 1 Subang) - Finni Puspita Dewi; Rd Sugara Mochamad Haddad (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2026)
The phenomenon of Fear of Missing Out (FoMO) has an impact on individuals’ attitudes and behaviors. Research by McKee et al. (2024) showed that FoMO can reduce moral awareness, thereby changing social responsibility behavior, such as neglecting obligations. This condition becomes a particular concern when experienced by adolescents. Based on observations at SMA PGRI 1 Subang, the researcher found several cases reflecting moral degradation in the form of declining responsibility, such as being late to school, failing to complete assignments given by teachers, using mobile phones in class when not needed, littering, lack of initiative both inside and outside the classroom, and low learning motivation. This study aims to determine the extent of the influence of FoMO on the decline of adolescent responsibility at SMA PGRI 1 Subang in the perspective of Civic Education. The theoretical foundation used in this research is Przybylski’s theory (2013) of FoMO and the concept of responsibility in Civic Education, which emphasizes aspects of discipline, initiative, and diligence. This research employed a quantitative approach with a survey method. The research sample consisted of 63 eleventh-grade students of SMA PGRI 1 Subang selected using a simple random sampling technique. The instrument used was a questionnaire, and the data were analyzed using simple linear regression. The results showed that the FoMO variable had a significant effect on adolescent responsibility, with the regression equation Y = 2.617 + 0.389X and a significance value of 0.000 < 0.05. This finding indicates that the higher the level of FoMO, the lower the responsibility possessed by adolescents. In conclusion, FoMO contributes significantly to the decline of adolescent responsibility, while Civic Education plays an important role in instilling responsibility, digital literacy, and self-control so that adolescents are able to face the challenges of the social media era.